2009
DOI: 10.1186/1471-2458-9-35
|View full text |Cite
|
Sign up to set email alerts
|

Trends in socioeconomic inequalities in cancer mortality in Barcelona: 1992–2003

Abstract: BackgroundThe objective of this study was to assess trends in cancer mortality by educational level in Barcelona from 1992 to 2003.MethodsThe study population comprised Barcelona inhabitants aged 20 years or older. Data on cancer deaths were supplied by the system of information on mortality. Educational level was obtained from the municipal census. Age-standardized rates by educational level were calculated. We also fitted Poisson regression models to estimate the relative index of inequality (RII) and the Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 60 publications
9
19
0
6
Order By: Relevance
“…Consistent with our findings, the risk of cervical cancer mortality in Quebec and urban Canada was 1.7 times higher in the poorest neighborhood income quintile than in the richest-income quintile [13, 55, 67]. Two recent studies reported marked educational inequalities in cervical cancer mortality in many European populations [11, 56]. …”
Section: Part IIsupporting
confidence: 90%
“…Consistent with our findings, the risk of cervical cancer mortality in Quebec and urban Canada was 1.7 times higher in the poorest neighborhood income quintile than in the richest-income quintile [13, 55, 67]. Two recent studies reported marked educational inequalities in cervical cancer mortality in many European populations [11, 56]. …”
Section: Part IIsupporting
confidence: 90%
“…This finding is consistent with most existing studies [16] [17]. People with a lower education level experience a higher burden of cancer [17].…”
Section: Discussionsupporting
confidence: 93%
“…Differences in patterns of cancer incidence and mortality are observed between areas with higher and lower social development worldwide [8]. The process of economic development stimulates advances in medical technology and improved access to health care, both for infectious and non-communicable diseases such as cancer [9].…”
Section: Introductionmentioning
confidence: 99%